Carbon sequestration and fertility after centennial time scale incorporation of charcoal into soil. - Irene Criscuoli; Giorgio Alberti; Silvia Baronti; Filippo Favilli; Cristina Martinez; Costanza Calzolari; Emanuela Pusceddu; Cornelia Rumpel; Roberto Viola; Franco Miglietta (PLoS ONE, 2014)
The addition of pyrogenic carbon (C) in the soil is considered a potential strategy to achieve direct C sequestration and potential reduction of non-CO2 greenhouse gas emissions. In this paper, we investigated the long term effects of charcoal addition on C sequestration and soil physico-chemical properties by studying a series of abandoned charcoal hearths in the Eastern Alps of Italy established in the XIX century. This natural setting can be seen as an analogue of a deliberate experiment with replications. Carbon sequestration was assessed indirectly by comparing the amount of pyrogenic C present in the hearths (23.3±4.7 kg C m(-2)) with the estimated amount of charcoal that was left on the soil after the carbonization (29.3±5.1 kg C m(-2)). After taking into account uncertainty associated with parameters' estimation, we were able to conclude that 80±21% of the C originally added to the soil via charcoal can still be found there and that charcoal has an overall Mean Residence Time of 650±139 years, thus supporting the view that charcoal incorporation is an effective way to sequester atmospheric CO2. We also observed an overall change in the physical properties (hydrophobicity and bulk density) of charcoal hearth soils and an accumulation of nutrients compared to the adjacent soil without charcoal. We caution, however, that our site-specific results should not be generalized without further study.